Malnutrition and Mortality in Frail and Non-Frail Older Adults Undergoing Aortic Valve Replacement. Issue 20 (13th November 2018) - Goldfarb, Michael; Lauck, Sandra; Webb, John G.; Asgar, Anita W.; Perrault, Louis P.; Piazza, Nicolo; Martucci, Giuseppe; Lachapelle, Kevin; Noiseux, Nicolas; Kim, Dae H.; Popma, Jeffrey J.; Lefèvre, Thierry; et al.
Abstract : Background: Older adults undergoing aortic valve replacement (AVR) are at risk for malnutrition. The association between preprocedural nutritional status and midterm mortality has yet to be determined. Methods: The FRAILTY-AVR (Frailty in Aortic Valve Replacement) prospective multicenter cohort study was conducted between 2012 and 2017 in 14 centers in 3 countries. Patients ≥70 years of age who underwent transcatheter or surgical AVR were eligible. The Mini Nutritional Assessment-Short Form was assessed by trained observers preprocedure, with scores ⩽7 of 14 considered malnourished and 8 to 11 of 14 considered at risk for malnutrition. The Short Performance Physical Battery was simultaneously assessed to measure physical frailty, with scores ⩽5 of 12 considered severely frail and 6 to 8 of 12 considered mildly frail. The primary outcome was 1-year all-cause mortality, and the secondary outcome was 30-day composite mortality or major morbidity. Multivariable regression models were used to adjust for potential confounders. Results: There were 1158 patients (727 transcatheter AVR and 431 surgical AVR), with 41.5% females, a mean age of 81.3 years, a mean body mass index of 27.5 kg/m 2, and a mean Society of Thoracic Surgeons-Predicted Risk of Mortality of 5.1%. Overall, 8.7% of patients were classified as malnourished and 32.8% were at risk for malnutrition. Mini Nutritional Assessment-Short Form scores were modestly correlated with Short Performance Physical Battery scores (Spearman R =0.31, P <0.001). There were 126 deaths in the transcatheter AVR group (19.1 per 100 patient-years) and 30 deaths in the surgical AVR group (7.5 per 100 patient-years). Malnourished patients had a nearly 3-fold higher crude risk of 1-year mortality compared with those with normal nutritional status (28% versus 10%, P <0.001). After adjustment for frailty, Society of Thoracic Surgeons-Predicted Risk of Mortality, and procedure type, preprocedural nutritional status was a significant predictor of 1-year mortality (odds ratio, 1.08 per Mini Nutritional Assessment-Short Form point; 95% CI, 1.01–1.16) and of the 30-day composite safety end point (odds ratio, 1.06 per Mini Nutritional Assessment-Short Form point; 95% CI, 1.001–1.12). Conclusions: Preprocedural nutritional status is associated with mortality in older adults undergoing AVR. Clinical trials are needed to determine whether pre- and postprocedural nutritional interventions can improve clinical outcomes in these vulnerable patients. Abstract : Supplemental Digital Content is available in the text.